Report on CIE-HKIE-IEM tripartite seminar on the management and case study on adjacent underground construction - Shong, Liew Shaw, Ir. (The Institution of Engineers, Malaysia (IEM), 2014)
Link to publisher’s homepage at http://www.myiem.org